Application of Diversion to Children as Perpetrators of Crimes of Sexual Violence Perspective of Positive Law and Islamic Law (Case Study at Jambi Police) - Tirta, Dhea Cakra (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This research was conducted to determine the application of diversion to children as perpetrators of criminal acts of sexual violence from the perspective of positive law and Islamic law at the Jambi Police. This study is normative legal research, with a comparative legal study approach and a legislative approach. The research results show that children are valuable assets for the nation and state, so that the future of the nation is determined by the next generation. In order to realize the protection of children's rights, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System or better known as the SPPA Law was created. In the SPPA Law there is a clause that is quite progressive to protect children's rights. namely the clause regarding diversion, where diversion is the resolution of children's cases outside of court which aims to protect children's rights and also to realize restorative justice for children. Diversion is carried out for the reason of providing law violators with an opportunity to become good people again through non-formal channels by involving community resources.